What is new in genetics and osteogenesis imperfecta classification? - Eugênia R. Valadares; Túlio B. Carneiro; Paula M. Santos; Ana Cristina Oliveira; Bernhard Zabel (Brazilian Society of Pediatrics, 2014)
Objective: Literature review of new genes related to osteogenesis imperfecta (OI) and update of its classification. Sources: Literature review in the PubMed and OMIM databases, followed by selection of relevant references. Summary of the findings: In 1979, Sillence et al. developed a classification of OI subtypes based on clinical features and disease severity: OI type I, mild, common, with blue sclera; OI type II, perinatal lethal form; OI type III, severe and progressively deforming, with normal sclera; and OI type IV, moderate severity with normal sclera. Approximately 90% of individuals with OI are heterozygous for mutations in the COL1A1 and COL1A2 genes, with dominant pattern of inheritance or sporadic mutations. After 2006, mutations were identified in the CRTAP, FKBP10, LEPRE1, PLOD2, PPIB, SERPINF1, SERPINH1, SP7, WNT1, BMP1, and TMEM38B genes, associated with recessive OI and mutation in the IFITM5 gene associated with dominant OI. Mutations in PLS3 were recently identified in families with osteoporosis and fractures, with X‐linked inheritance pattern. In addition to the genetic complexity of the molecular basis of OI, extensive phenotypic variability resulting from individual loci has also been documented. Conclusions: Considering the discovery of new genes and limited genotype‐phenotype correlation, the use of next‐generation sequencing tools has become useful in molecular studies of OI cases. The recommendation of the Nosology Group of the International Society of Skeletal Dysplasias is to maintain the classification of Sillence as the prototypical form, universally accepted to classify the degree of severity in OI, while maintaining it free from direct molecular reference.